(untitled) (Global Journal of Science Frontier Research, 2017)
The aim of this research was to evaluate the impact of lead nitrate on soil microbial activities, growth performance, and the phytoremediation potential of Vigna unguiculata (cowpea) grown in agricultural soil. Pristine sandy loam soils were polluted with nitrate salt of lead at four different levels (50mg/kg, 100mg/kg, 200mg/kg and 400mg/kg) in triplicates. A significant (P < 0.05) retarding effect of the metal salt on the studied parameters was observed. Consistently, total bacterial population was found decreasing with rise in lead dosage. Lead was also found to significantly (P < 0.05) affect the microbial metabolism as witnessed by the lowering of CO 2 evolved in the test samples.